Food system sustainability : insights from duALIne - Esnouf, Catherine, 1956-; Russel, Marie; Bricas, N. (Nicolas) (Cambridge : Cambridge University Press, 2013)
'As western-style food systems extend further around the world, food sustainability is becoming an increasingly important issue. Such systems are not sustainable in terms of their consumption of resources, their impact on ecosystems or their effect on health and social inequality'--
Includes bibliographical references (pages 247-385) and index.
Keywords: Food industry and trade; Sustainable development